Macroeconomic Modelling of R&D and Innovation Policies - Akcigit, Ufuk; Benedetti Fasil, Cristiana; Impullitti, Giammario; Licandro, Omar; Sanchez-Martinez, Miguel (International Economic Association Series, 2022)
This open access book encompasses a collection of in-depth analyses showcasing the challenges and ways forward for macroeconomic modelling of R&D and innovation policies. Based upon the proceedings of the EC-DG JRC-IEA workshop held in Brussels in 2017, it presents cutting-edge contributions from a number of leading economists in the field. It provides a comprehensive overview of the current academic and policy challenges surrounding R&D as well as of the state-of-the-art modelling techniques. The book brings to the forefront outstanding issues related to the assessment of the macroeconomic impact of R&D policies and its modelling. It speaks to the rising importance of R&D and innovation policy, and the proliferation of macroeconomic models featuring endogenous technological change. The contents of this book will be of interest to both academic and policy audiences working in the fields of R&D and innovation.